Real Work Lecture: (GERMAS) Zero Waste Healthy House Movement Through Magot Cultivation Innovation and as a New Superior Entrepreneurial Product in Improving the Welfare of MSMEs in Glindah Village - Raura, Anisa; Mustofa, Almira Rizka; Inayah, Nailul; Ronia, Ziatun Nur; Muzaki, Feri Ihsan (Journal of Health Community Service, 2023)
The Zero Waste Healthy Home Movement has become the main focus in efforts to create a clean, healthy and sustainable environment. In an effort to achieve this goal, magot cultivation innovation is a promising solution. This study aims to describe the role of maggot cultivation as part of the Zero Waste Healthy Home Movement and its potential as a new leading entrepreneurial product in improving the welfare of MSMEs. Maggot, as a processed product from organic waste, has high economic and ecological added value. Maggot-based products can be marketed as high quality organic fertilizers that are environmentally friendly, as well as various other products such as animal feed and health products. Through magot cultivation innovations, MSMEs have the opportunity to earn additional income and improve the welfare of residents in Glindah Village